2019
DOI: 10.1111/dmcn.14141
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve upper limb function for children with bilateral cerebral palsy: a systematic review

Abstract: AimTo systematically review the efficacy of interventions on upper limb function in children 0 to 19 years of age with bilateral cerebral palsy on the basis of outcome measures of upper limb function and measures of activities and/or participation according to the International Classification of Functioning, Disability and Health.MethodCochrane, PubMed, Embase, CINAHL, and Web of Science were searched from inception to September 2017. Methodological quality and strength of evidence were analysed by two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 87 publications
0
35
0
4
Order By: Relevance
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…Primary and secondary impairments contributing to reduced development of the reach for, grip, and manipulation of objects affect self-care activities, such as drinking, feeding, grooming, dressing, and writing [6]. These impairments and functional limitations can affect the child's education, often leading to participation restriction [7].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned associated and accompanying disorders in the clinical picture of CP have an additional or aggravating effect on the developmental capacity of the child to learn and perform everyday tasks. Consequently, the improvement of functional abilities and the gradual increase of independence in activities of everyday life is undoubtedly one of the key goals of their rehabilitation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of mobility and self-care, including the independence level, are usually examined only in relation to gross motor abilities or in relation to gross motor and fine manual abilities [5,[8][9][10][11][12]. Besides, the effects of different types of treatment were examined and the factors influencing the development of functional independence in children with CP identified [6,7,13,14]. In other words, DOI: https://doi.org/10.2298/SARH190321077M previous empirical research did not take into account the overall profile of motor abilities of children with CP that, in addition to both gross motor function and manual abilities, includes bimanual fine motor function.…”
Section: Introductionmentioning
confidence: 99%